A density-tunable liquid-phase microextraction system based on deep eutectic solvents for the determination of polycyclic aromatic hydrocarbons in tea, medicinal herbs and liquid foods. (1st August 2021) - Deng, Wenwen; Huang, Anqi; Zheng, Qutong; Yu, Long; Li, Xiao; Hu, Hankun; Xiao, Yuxiu
Highlights: A novel density-tunable LPME system based on HFIP-DESs was proposed. DES-rich phase can be induced to form in the bottom or in the top of the system. The system is suitable for directly extracting PAHs from both liquid and solid foods. The LPME method is simple, rapid and only consumes small amount of organic solvents. Abstract: A novel density-tunable liquid-phase microextraction (DT-LPME) system was developed with high-density deep eutectic solvents (DESs) as extractant and low-density organic solvents as emulsifier and density regulator. DES-rich phase was induced to form in the bottom or in the top by adjusting the emulsifier amount. This system was used to directly extract polycyclic aromatic hydrocarbons (PAHs) from liquid and solid foods, and the obtained DES-rich phase was easy to be collected for quantification. The method (LPME with HPLC-fluorescence detector) has linearity (R 2 > 0.9974), detection limits of 0.6–4.2 ng L -1 for liquid foods and 0.05–0.35 ng g −1 for solid foods, recoveries of 86.2–114.9%, and intra-day/inter-day RSDs below 6.6%. The method was applied to detect PAHs in real samples, and the PAHs residue was found in honey and five solid foods. The DT-LPME method is simple, fast, green and suitable for direct extraction of analytes from both liquid and solid samples.